Estilos de aprendizagem nas organizações de tecnologia: uma visão sob a lente de David Kolb - Rodrigues, Eduardo Alexandre (2020)
Knowing the Learning Styles of individuals working in Technology organizations can be a competitive factor for this segment, not only to appropriate the knowledge of these individuals, but also to maximize the results and also their qualification. As a result of a variety of existing Learning Styles, as well as a new need to consider them within the teaching and learning process, we chose the theoretical model for Experiential Learning by David Kolb so that the characteristics of individual styles and modes were identified. We identified the need for this study, not only due to the intention of knowing the Learning Styles that emerge in technology organizations, but we also identified a gap regarding the theme. A 2019 bibliometric survey showed that the topic is still poorly addressed in the area of Administration. The authors of this study found only 18 articles referring to the study of Management Learning Styles. The instruments used to collect data from this research work were not only the analysis of a bibliographic research on the topic, but also the use of a questionnaire called Learning Styles Inventory, prepared by David Kolb, to 211 respondents who work in Technology companies in three countries. The results showed that the researched groups were heterogeneous. Men with the largest number, with 137 respondents, and women with 74 respondents. Most between the ages of 31 to 40 years and between 21 to 30 years. There is no predominance of the Convergent Learning Style as a characteristic of the theory described by Kolb, where individuals with Convergent characteristics are predominant in the performance in technology. In turn, the female gender showed prominence and significance in the results in terms of the Learning Styles, Accommodating and Assimilating, the latter being more significant in terms of samples, and confirming the relationship between individual characteristics and learning styles.